2011
DOI: 10.1590/s1678-58782011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a porous-inclined slider bearing lubricated with magnetic fluid considering thermal effects with slip velocity

Abstract: A theoretical model of a porous-inclined slider bearing lubricated with magnetic fluid has been considered together with slip velocity boundary condition. Our aim is to study the influence of various dimensionless parameters arising out of the analysis of the model. By assuming the viscosity µ = µ0 exp [-β(t m - t0)] of magnetic fluid, the expressions for mean temperature and load capacity have been obtained. It has been observed that both mean temperature field and load capacity are the functions of slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Thermal variation theories of nanofluids and experimental conclusions on the thermal properties of nanofluids have been studied by many authors. 1928…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal variation theories of nanofluids and experimental conclusions on the thermal properties of nanofluids have been studied by many authors. 1928…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the enhanced heat transfer properties of ferro-nanofluids, many authors have investigated the behaviours of ferro-nanofluid flows. Ahmed et al 25 have highlighted the importance of the ferro-nanofluid flow in slider bearings using the Rosensweig model. They have discussed the load-carrying capacity and mean temperature using temperature-dependent viscosity and have explained the importance of the heat transfer rate in bearings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993 N. M. Bujurke [6] and his associates studied the circular porous slider through computer extended series. Recent developments about slider bearing can be obtained from the articles [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The graphical results showed that for huge values of aspect ratio, slip had a substantial impact. Some researchers [22,23,24,25,26,27] have also used magnetic fluid as a lubricant in order to aid the Tribological performance of a different sliding interface. [28] dealt with the impact of squeeze film of step bearing with magnetic fluid.…”
Section: Introductionmentioning
confidence: 99%